Contrasted effect of biochar and earthworms on rice growth and resource allocation in different soils - Noguera, D; Rondón, Marco Antonio; Laossi, KR; Hoyos Villegas, Valerio; Lavelle, Patrick M.; Carvalho, M.H.C. de; Barot, Sébastien (Elsevier, 2010)
Adding biochar to soils and maintaining high earthworm biomasses are potential ways to increase the fertility of tropical soils and the sustainability of crop production in the spirit of agroecology and ecological engineering. However, a thorough functional assessment of biochar effect on plant growth and resource allocations is so far missing. Moreover, earthworms and biochar increase mineral nutrient availability through an increase in mineralization and nutrient retention respectively and are likely to interact through various other mechanisms. They could thus increase plant growth synergistically. This hypothesis was tested for rice in a greenhouse experiment. Besides, the relative effects of biochar and earthworms were compared in three different soil treatments (a nutrient rich soil, a nutrient poor soil, a nutrient poor soil supplemented with fertilization). Biochar and earthworm effects on rice growth and resource allocation highly depended on soil type and were generally additive (no synergy). In the rich soil, there were both clear positive biochar and earthworm effects, while there were generally only positive earthworm effects in the poor soil, and neither earthworm nor biochar effect in the poor soil with fertilization. The analysis of earthworm and biochar effects on different plant traits and soil mineral nitrogen content, confirmed that they act through an increase in nutrient availability. However it also suggested that another mechanism, such as the release in the soil of molecules recognized as phytohormones by plants, is also involved in earthworm action. This mechanism could for example help explaining how earthworms increase rice resource allocation to roots and influence the allocation to grains.